The Evaluation of Parental Acceptance Towards Children with Sex Chromosomal Disorders of Sex Development Using A Mixed-Method - Iit Fitrianingrum (Diponegoro University, 2021)
Background: Sex chromosomal Disorder of sex development (DSD) is an atypical abnormality of external genitalia which is mismatched with its sex chromosome traits. The condition of children with DSD affects the dynamics in the family. Parents’ reactions after discovering this health problem vary greatly, such as being in a state of shock, confusion, or self-blame. However, parents’ acceptance is extremely important for better quality of caring, to the healthy social and emotional child development, and to make the best decisions regarding gender assignment.